Detailed analysis of pro-apoptotic signaling and metabolic adaptation triggered by a N-heterocyclic carbene-gold(I) complex - Holenya, Pavlo; Can, Suzan; Rubbiani, Riccardo; Alborzinia, Hamed; Zeilfelder, Anja; Cheng, Xinlai; Ott, Ingo; Wölfl, Stefan (Metallomics, 2014)
Due to their broad spectrum of biological activity and antiproliferative effect on different human cancer cell lines, gold compounds have been in the focus of drug research for many years. Gold(I)-N-heterocyclic carbene complexes are of particular interest, because of their stability, ease of derivatization and clear cytotoxicity in cancer cells. To obtain a more detailed view of the molecular mechanisms underlying their cellular activity, we used a novel gold(I)-N-heterocyclic carbene complex, [triphenylphosphane-(1,3-diethyl-5-methoxy-benzylimidazol-2-ylidene)]gold(I) iodide and investigated changes in cellular signaling pathways using quantitative signal transduction protein microarray analysis. We also analyzed changes in cell metabolism in a time-dependent manner by on-line metabolic measurements and used isolated mitochondria to elucidate the direct effects on this cell organelle. We found strong cytotoxic effects in cancer cells, accompanied by an immediate and irreversible loss of mitochondrial respiration as well as by a crucial imbalance of the intracellular redox state, resulting in apoptotic cell death. ELISA microarray analysis of signal transduction pathways revealed a time-dependent up-regulation of pro-apoptotic signaling proteins, e.g. p38 and JNK, whereas pro-survival signals that are directly linked to the thioredoxin system were down-regulated, which pinpoints to thioredoxin reductase as a central target of the compound. Further results suggest that DNA is an indirect target of the compound. Based on our findings, we outline a signaling model for the molecular mechanism underlying the antiproliferative activity of the gold(I)-N-heterocyclic carbene complex investigated, which provides a good general model for the known pattern of cell death induced by this class of substances.
Gesehen am 25.09.2020